Plant Cryopreservation - Benelli, Carla (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Cryopreservation is the storage of cells, tissues and organs at ultra-low temperatures (−196 °C) and can be an important tool for long-term conservation of plant genetic resources. A wide range of cryogenic procedures have been developed for in vitro explants, dormant buds and non-orthodox seeds in many plant species; however, research that provides novelty, insight and advances for developing and improving new protocols in plant species is still needed. This book includes the development of new protocols, physical and chemical studies related to preservation in liquid nitrogen, and some reviews on several aspects of cryopreservation. This publication will be a useful document for the community of cryopreservation scientists.